Making Federalism Work : The 18th Constitutional Amendment - Shah, Anwar (World Bank, Washington, DC, 2014)
The almost unanimous passage of a landmark consensus constitutional amendment "the 18th Constitutional Amendment" restored Pakistan's constitution to its original intent of a decentralized federation of four provinces as envisaged in the 1956 and 1973 constitutions. This amendment was hailed by policy makers and academics alike as a major step forward in reforming the multi-order governance in Pakistan. This paper takes a closer look at the provisions of this amendment and highlights both the potentials and pitfalls of the new constitutional order for good governance in Pakistan. The paper concludes that the amendment must be seen as a first yet small and incomplete step in reforming multi-order governance in Pakistan. A large unfinished reform agenda remains to be charted.